Investigating the behavioural intention to adopt flipped learning: a study from ESL lecturers’ perspective - Chew, Zhi Jun (2022)
Following the trend of online learning, flipped learning has increasingly received attention in the educational field, including second language learning. Previous research has mainly focused on the students’ perspectives and the effectiveness of the approach. Since instructors are the implementers of flipped learning, this study sought to investigate factors which could affect ESL lecturers’ behavioural intentions in adopting the approach. It also explored how ESL lecturers perceive flipped learning. Using UTAUT as the theoretical lens, this mixed-methods research involved questionnaire survey and semi-structured interviews. The sample consisted of 48 ESL lecturers from five different higher education institutions. Results of multiple linear regression analysis showed that performance expectancy and facilitating conditions are factors that significantly influence behavioural intention to adopt flipped learning. The benefits of flipped learning and several issues concerning adoption of the approach were revealed during the interview sessions. The findings provide insight to stakeholders in suggesting ways to encourage the use of flipped learning. Similar research can be done in the future by involving a larger number of participants from different private higher education institutions.